Mental health literacy among secondary school learners in Tshwane region 1: A quantitative study - Dumisile P. Madlala; Pierre Joubert; Oratilwe P. Mokoena (South African Journal of Psychiatry)
Background: Mental health literacy (MHL) is one of the crucial factors in the prevention and maintenance of youth mental health. Despite this fact, there is limited research on MHL in this age group.